Araw ng patay fiesta ng mga buhay - Aguilar, Mila D.; Selvido, Ma. Ernie ([Quezon City] Institute for Filipino Cinema, 1989)
Shows how November 1, All Souls' Day, becomes a feast for the living in fun-loving Philippines. Documents an interview with poor families living in La Loma Cemetery.
VHS
Host, Ma. Ernie Selvido; editor, Mel L. Bacani III.
Keywords: All Souls' Day -- Philippines; Sociology